A COMPREHENSIVE REVIEW OF ROUTING PROTOCOLS FOR MOBILE AD HOC NETWORKS (MANETS) - Augustine Chidiebere Onuora; Eyo Edmund Essien; Prince Ana (IJISCS (International Journal of Information System and Computer Science), 2022)
Network routing has been one of the most investigated areas in computing networking for decades. Many studies on wired and wireless networks have been conducted. More research fields for network routing technology have emerged as a result of recent technological advancements. In recent years, research into ad hoc networks such as wireless sensor networks (WSN), vehicular ad hoc network (VANET), wireless mesh network (WMN), and mobile ad hoc network (MANET) has increased. Due to the mobile nature of a lot of gadgets we use this days, the researchers embarked on a review to comprehensively show the various routing protocol technology that one can adopts when implementing a network routing scheme for MANETs. Types of routing protocols, classifications, routing techniques, geographical coverage, route metric, route repository and route reconfiguration strategies are covered in detail. The various routing protocols covered in this study were compared in this paper. The protocols' areas of strength were highlighted and network simulators that had these protocols enabled by default were also x-rayed.